Bending of a Stepped Sandwich Beam: The Shear Effect - Joanna KUSTOSZ; Krzysztof MAGNUCKI; Damian GOLIWĄS (Engineering Transactions, 2022)
This paper is devoted to the stepped sandwich beam with clamped ends subjected to a uniformly distributed load. The bending problem of the beam is formulated and solved with consideration of the classical sandwich beam of constant face thickness. Two differential equations of equilibrium based on the principle of the stationary potential energy of the classical beam are obtained and analytically solved. Moreover, numerical-FEM models of the beams are developed. Deflections for an exemplary beam family with the use of two methods are calculated. The results of the study are presented in figures and tables.